Use of e-toll Cards: Satisfied Consumers? - Sa’diyah, Wachidatus; Marlena, Novi (JURNAL MANAJEMEN MOTIVASI, 2018)
The application of toll road electronification aims to provide satisfaction for toll road users in the making transactions faster and efficiently without having to queue. The study of the effectiveness of the e-toll card program is noteworthy because of the success or failure of the quality of services provided by the company; it will show an increase in the satisfaction of toll users, which in turn will become the benchmark of the company in managing services. The purpose of this study was to determine the effect of e-toll card program effectiveness on customer satisfaction of toll road users on the Surabaya-Gempol toll road. The study sample was 400 respondents, for data analysis techniques using simple linear regression. The results showed that the effectiveness of the e-toll card program affected the satisfaction of toll road users.